The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.44922
|View full text |Cite
|
Sign up to set email alerts
|

Structure, bioactivities and applications of the polysaccharides from Tricholoma Matsutake: a review

Abstract: Tricholoma Matsutake is an important edible mushroom that has been artificially cultivated and used as a food and medicinal ingredient in traditional Chinese medicine. In the past decades, many researchers have reported that Tricholoma Matsutake Polysaccharides (TMP) possess various bioactivities, including anti-tumor, immunomodulatory, anti-oxidation and anti-aging. The structural characteristics of TMP were studied by GC-MS, LC-MS, NMR, and FT-IR, and the structure-activity relationship of TMP biomolecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The most common way to produce bioactive peptides is through enzymatic hydrolysis of whole protein molecules (Li et al, 2022). In our study, edible meat from C. fluminea was enzymatically hydrolyzed with commercial enzymes for the preparation of functional peptides, the %DH value was around 15%.…”
Section: Preparation and Characteristic Of The Cphmentioning
confidence: 88%
“…The most common way to produce bioactive peptides is through enzymatic hydrolysis of whole protein molecules (Li et al, 2022). In our study, edible meat from C. fluminea was enzymatically hydrolyzed with commercial enzymes for the preparation of functional peptides, the %DH value was around 15%.…”
Section: Preparation and Characteristic Of The Cphmentioning
confidence: 88%
“…It can be seen that the edible fungus industry has broad market prospects. Studies have confirmed that edible fungi contain a variety of bioactive substances, such as polysaccharides (Li et al, 2022), proteins (González et al, 2020), terpenoids (Zhao et al, 2020;Guofeng et al, 2020), vitamins (Mingqing et al, 2020), minerals (Liu, 2018), etc., and these active substances can play a vital role in the human body (Zhang et al, 2020b;Nhi et al, 2022). Among them, edible fungus polysaccharide is undoubtedly a research hotspot in recent years.…”
Section: Introductionmentioning
confidence: 97%
“…Edible coatings with good oxygen isolation and antibacterial properties are used as a common material in coating preservation. Polysaccharides are long and complex chain carbohydrates with different functional and biological activities due to differences in structural characteristics (Li et al, 2022). The functional activity of coating film is one of the many activities of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%